Acute Febrile Illnesses – Clinico-epidemiological Pattern in a Remote Geographical Location of North-eastern India - Monya Michi (International Journal of Medical Research and Review, 2023)
Background: Acute undifferentiated febrile illness (AUFI / AFI) is a common cause for patients seeking hospital care in tropical country like India. Non-specificity of symptoms and lack of appropriate diagnostics pose challenge especially in resource limited settings. Investigation into etiology and trends of AUFI provide valuable public health data to target clinical workup and guide optimal treatment.Method: A record based descriptive study was conducted on all AFI cases presenting to a Government tertiary care centre in a tribal hilly sate of Northeast India in the year 2021.Result: Under five children were the most affected and respiratory infections were the most common cause of fever. Enteric fever and scrub typhus were the most common cause of undifferentiated fever. However, it was a remarkable finding that no case of malaria or dengue was reported from this region. Fevers remained undetermined in 28% of cases. Undetermined fevers and scrub typhus had higher occurrence during winters while no seasonality was observed with enteric fever. Majority of the patients recovered and discharged. Case fatality rate was 0.35%.Conclusion: The local epidemiology of AUFI can help guide presumptive diagnosis and deliver optimal patient management in these settings. Typhoid and scrub typhus to be considered as differentials for AUFI in this region.